2018
DOI: 10.2174/1567201814666171013150534
|View full text |Cite
|
Sign up to set email alerts
|

Nanomedicine for Intranasal Delivery to Improve Brain Uptake

Abstract: Intranasal drug delivery system provides distinct advantage over conventional drug delivery system for a drug that is pharmacokenetically or biologically unstable. Major concern for the treatment of central nervous system diseases is, low concentration of therapeutically active molecule within brain as blood brain barrier is creating obstacle, where intranasal drug delivery provides direct transport of therapeutically active moiety into brain via olfactory or trigeminal pathway. Nasal mucosa provides distinct … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 27 publications
(10 citation statements)
references
References 0 publications
0
10
0
Order By: Relevance
“…Another possible approach in the administration of PENs, intranasal administration, has been demonstrated. Intranasal administration has been commonly used for the treatment of pulmonary disease, and it provides advantages such as allowing local delivery; the delivery of a concentrated dose to the target organ; and direct delivery to the respiratory system, the upper nose, and brain [ [121] , [122] , [123] , [124] , [125] 126 ]. Zhuang et al reported the use of intranasal route-based GNV and miRNA targeting brain tumor [127] .…”
Section: Applications Of Pens and Their Therapeutic Effectsmentioning
confidence: 99%
“…Another possible approach in the administration of PENs, intranasal administration, has been demonstrated. Intranasal administration has been commonly used for the treatment of pulmonary disease, and it provides advantages such as allowing local delivery; the delivery of a concentrated dose to the target organ; and direct delivery to the respiratory system, the upper nose, and brain [ [121] , [122] , [123] , [124] , [125] 126 ]. Zhuang et al reported the use of intranasal route-based GNV and miRNA targeting brain tumor [127] .…”
Section: Applications Of Pens and Their Therapeutic Effectsmentioning
confidence: 99%
“…Most of these treatments for neurodegenerative diseases simply reduced the disease’s progression rather than curing it entirely. Majority of hydrophilic compounds are unable to cross the BBB, owing to the presence of the efflux transporters like P-glycoprotein (P-gp) and other multi-drug-related protein transporters ( Matsumoto et al, 2017 ; Patel et al, 2018 ). Due to their poor ability to cross the BBB, high first-pass effect, and frequent off-site targeting ( Goel et al, 2022 ), and prospective peptide-based ( Ayyalasomayajula and Suresh, 2018 ; Trapani et al, 2018 ) or gene delivery ( Malhotra et al, 2013 )-based therapies continue to be in the translational phase ( Goel, et al, 2022 ).…”
Section: Alzheimer’s Diseasementioning
confidence: 99%
“…Several nasally administered formulations proved their efficacy for delivering drugs to the brain in NDs [459][460][461][462][463][464]. The nanosystems mainly used are nanoemulsions [465,466] and liposomes [467,468], but also polymeric NPs [469] and SLNs [470].…”
Section: Nanosystems For Nose-to-brain Drug Delivery In the Treatment...mentioning
confidence: 99%